Sustainable Use of Steel Macrofibers and Polypropylene Microfibers Combined with Nanosilica for Precast Concrete Pavements in Underground Mining - Brescia-Noranmbuena, L (American Society of Civil Engineers, 2025)
The sustainable development of mining and innovation in concrete pavements for underground mining motivate the use of new additives in concrete applicable to prefabricated construction systems. According to the literature, it is possible to use a combination of mixed fibers with the addition of nanosilica (NS) to mitigate strength losses that affect concretes. This research evaluates the use of steel macrofibers (MF) and polypropylene microfibers (mF) in concretes with the addition of nanosilica, determining the synergy or competition of these materials on parameters such as the strength, durability, and environmental impact of precast pavements in underground mining. A 24+1 factor analysis was performed, incorporating the central point and control mixtures as variables, including the water-to-cementitious material ratio, the percentage of NS replacement for cement, and the dosages of MF and mF. The evaluation included settling, compressive strength at 7 and 28 days, flexural strength at 28 days, abrasion resistance at 28 days, and surface resistivity at 7 and 28 days. The responses were then incorporated into a structural design of precast underground mining pavements, resulting in different pavement thicknesses for each mixture. Subsequently, the environmental impact of each mixture was evaluated by calculating the equivalent CO2 parameter. The results demonstrated synergy in the combined use of additives, enhancing the strength and durability parameters while simultaneously reducing the environmental impact of underground mining pavements. Consequently, using MF and NS in concrete improved the pavements performance and can reduce the CO2 equivalent emissions by approximately 50%. © 2025 American Society of Civil Engineers.